Zakat For Food Security: Study Of The Baznas Zakat Distribution In Ternate - Syaifuddin Syaifuddin; Muhammad Ufuqul Mubin; Muh. Sajjaj Sudirman (Universitas Islam Darul 'ulum Lamongan, 2026)
This research aims to analyze the role of BAZNAS in Ternate city in strengthening food security. The zakat management institution established in the city of Ternate in 2010 has five superior programs, namely: Ternate Taqwa, Prosperity, Health, Smartness and Caring. In developing food security, BAZNAS, the city of Ternate accommodates this in the Ternate Sejahtera program. The type of research used is qualitative research. Research location at BAZNAS, Ternate city. The types and sources of data consist of primary and secondary data which researchers obtained through interviews, voice recorders, taking written data, taking pictures and so on. Researchers carry out data analysis and data management techniques by arranging, grouping and describing the data and then drawing conclusions inductively, deductively and comparatively. Based on the research results, it can be found that the management of zakat in developing food resilience which is carried out by strengthening micro and small businesses is considered to be running in accordance with the orders of law and religion because these zakat funds are managed well and can have a positive impact on economic growth, because they have a purpose. clear and appropriate targets, it's just that the distribution of zakat proceeds is not evenly distributed to the people of Ternate city who, judging from their economic background, are less well off. This is proven based on the number of mustahik who receive business capital assistance from BAZNAS in Ternate city, which decreases every year. Keywords: Zakat Distribution, Food Security, BAZNAS.